Chromatography :Basic Principles,Sample Preparations and Related Methods - Lundanes, Elsa (Wiley-VCH, 2014)
This is a text on chromatography which is easy to grasp for undergraduates and technicians. The book includes all recent technology advances and has core textbook features further improving the learning experience.